JCT contract administration pocket book - Atkinson, Andy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is quite simply about contract administration using the JCT contracts. The key features of the new and updated edition continue to be its brevity, readability and relevance to everyday practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Superintendence -- Great Britain -- Handbooks, manuals, etc; Construction industry -- Subcontracting -- Great Britain -- Handbooks, manuals, etc; Construction contracts -- Great Britain -- Handbooks, manuals, etc; LAW / Construction; ARCHITECTURE / Project Management